The cosmological milk shake : a semi-serious look at the size of things - Ehrlich, Robert, 1938- ([New Brunswick, NJ] : Rutgers University Press, 1994)
Entertaining essays and cartoons explain the sizes of materials in the universe and modern physics.
Includes bibliographical references (p. 253-254) and index.
Booklist.
Library Journal.
University Press Titles (A.A.S.L./P.L.A.).
Adult.
Adult
Keywords: Astrophysics -- Miscellanea; Physics -- Miscellanea; Physics -- Study and teaching; Size judgment -- Miscellanea; Astrophysics -- Miscellanea; Physics -- Miscellanea; Physics -- Study and teaching; Size -- Miscellanea